Use of caffeinated substances and risk of crashes in long distance drivers of commercial vehicles: case-control study - Sharwood, L.; Elkington, J.; Meuleners, Lynn; Ivers, R.; Boufous, S.; Stevenson, M. (BMJ Group, 2013)
Objective: To determine whether there is an association between use of substances that contain caffeine and the risk of crash in long distance commercial vehicle drivers.Design: Case-control studySetting: New South Wales (NSW) and Western Australia (WA), Australia.Participants: 530 long distance drivers of commercial vehicles who were recently involved in a crash attended by police (cases) and 517 control drivers who had not had a crash while driving a commercial vehicle in the past 12 months.Main outcome measure: The likelihood of a crash associated with the use of substances containing caffeine after adjustment for factors including age, health disorders, sleep patterns, and symptoms of sleep disorders as well as exposures such as kilometres driven, hours slept, breaks taken, and night driving schedules.Results: Forty three percent of drivers reported consuming substances containing caffeine, such as tea, coffee, caffeine tablets, or energy drinks for the express purpose of staying awake. Only 3% reported using illegal stimulants such as amphetamine (“speed”); 3,4 methylenedioxymethamphetamine (ecstasy); and cocaine. After adjustment for potential confounders, drivers who consumed caffeinated substances for this purpose had a 63% reduced likelihood of crashing (odds ratio 0.37, 95% confidence interval 0.27 to 0.50) compared with drivers who did not take caffeinated substances.Conclusions: Caffeinated substances are associated with a reduced risk of crashing for long distance commercial motor vehicle drivers. While comprehensive mandated strategies for fatigue management remain a priority, the use of caffeinated substances could be a useful adjunct strategy in the maintenance of alertness while driving.